Analyzing real flows performance in MANET using dynamic queue. Issue 6 (18th August 2017) - Verma, Sourabh Singh; Kumar, Anil; Patel, R. B.
Abstract: In current scenario real traffic demand for multimedia traffic has been increased. I t requires strict QoS. Performance may be degraded due to attacks like flooding request. In this article, we have done extensive analysis of our earlier proposed method, known as Real Flow Dynamic Queue (RFDQ), using several metrics and parameters, in attack and non-attack scenarios, our results demonstrate the performance of AODV-RFDQ is much better then AODV-PQ(Priority Queue), with metrics like delay, packet loss, bandwidth and throughput with different parameter like CBR interval, queue size and simulation time.